High Potential Columnar Nanocrystalline AlN Films Deposited by RF Reactive Magnetron Sputtering - Han, Chengzhang; Chen, Da; Zhang, Yaozhong; Xu, Dong; Liu, Yijian; Kong, Eric Siu-Wai; Zhang, Yafei (Nano-Micro Letters, 2012)
Columnar nanocrystalline aluminum nitride (cnc-AlN) thin films with (002) orientation and uniform texture have been deposited successfully on large silicon wafers by RF reactive magnetron sputtering. At the optimum sputtering parameters, the deposited cnc-AlN thin films show a c-axis preferred orientation with a crystallite size of about 28 nm and surface roughness (RMS) of about 1.29 nm. The cnc-AlN thin films were well transparent with an optical band gap about 4.8 eV, and the residual compressive stress and the defect density in the film have been revealed by Ramon spectroscopy. Moreover, piezoelectric performances of the cnc-AlN thin films executed effectively in a film bulk acoustic resonator structure.